Exploring counterintuitiveness: template- and schema-level effects - Gregory, J; Justin Gregory (2014)
Pascal Boyer’s theory of counterintuitive cultural representations asserts that concepts that violate developmentally natural intuitive knowledge structures demand more attention and are more transmittable than other concepts (Boyer and Ramble 2001: 535-64). Grounded in an empirically justified framework of ontological domain knowledge, counterintuitive representations have been identified across human cultures as consistently prevalent in religious beliefs and widely known folktales. Indeed, the ubiquity of counterintuitive representations of supernatural agents in world religions has led some to reason that its presence is a defining factor of “religion” (Atran 2002; Boyer 1994, 2001; Brown 1991; Pyysiäinen, Lindeman and Honkela 2003). The theory has attracted considerable attention from scholars. Boyer discussed and predicted the mnemonic advantages of culturally “familiar” counterintuitive representations (Boyer 2001: 58-105), yet this integral aspect has been poorly investigated, especially because subsequent free-recall studies have focused on novel representations that similarly violate assumptions about our intuitive ontologies. These studies have suffered from a variety of other shortcomings: small sample sizes that poorly represent population demographics and age ranges (most recruited university students); limited investigation of different modes of cultural transmission (most centred on written stimuli); emphasis on free recall at the expense of other measures of memory; and incomplete research into interactions of schema-level effects (e.g. positive and negative emotion, imagery, humour, and inferential potential) on the memorability of counterintuitive ideas. Although the theory claims universality across human cultures, purported differences between holistic and analytic types of cognition suggest that it is likely that East Asians process counterintuitive ideas differently from Westerners. But until this dissertation no data had yet been collected in East Asia. Hence, a large age-representative sample (N = 940), for three studies in both the UK and China, was used to investigate the interaction of template- and schema-level effects for wider forms of transmission biases endemic to cultural groups. The investigation comprised the interaction of the mnemonic effects of familiarity and counterintuitiveness and the impact of schema-level effects, employing a mixing of presentation media (Study #1), template-level preferences when generating schema-level ideas (Study #2), and transmission advantages for supernatural agents (Study #3). Study #1 consisted of two free-recall experiments: a minimal condition (subject-predicate statement) and elaborated condition (additional descriptive elements) of stimuli structure. The results were analysed by hierarchical linear model (HLM), with familiarity, counterintuitiveness, and delay as 2-level fixed factors, and age and schema-level effects as covariates. The findings revealed mixed support for predictions of the typical formulation of Boyer’s hypothesis. However, subsequent analyses revealed a significant interaction of counterintuitiveness x age and of counterintuitiveness x familiarity, for all conditions and cultural sites. Schema-level effects were also found to predict recall rate. Study #2 investigated template-level biases in a statement generation task. An analysis of covariance (ANCOVA) considering counterintuitiveness and the covariate of age revealed that children are significantly more likely to author counterintuitive ideas than older adults, in both UK and China. Study #3 (comparable in design to Study #1) found a significant interaction of counterintuitiveness x ontological category, revealed to be due to participants’ better recall rates, at both locations, for counterintuitive concepts belonging to the ontological category PERSONS. In summary, it appears that the counterintuitive effect is not as straightforward as it has been thought to be, and requires further theoretical development and empirical research to improve understanding about the interactive role of age, schema-level effects, and ontological category in the transmission and cultural epidemiology of such representations.